Evaluasi Pemberlakuan Sistem Aplikasi Keuangan Tingkat Instansi Dalam Rangka Mendukung Pertanggungjawaban Keuangan Di Satuan Kerja Perwakilan Republik Indonesia Di Luar Negeri-Kementerian Luar Negeri Republik Indonesia - Hilda, Hilda; Cholik, M. Agus (Neraca : Jurnal Akuntansi Terapan, 2024)
This study aims to analyze and evaluate the implementation of the SAKTI application, identify inhibiting factors, and assess the efforts made to overcome these obstacles and improve the SAKTI system in relation to its implementation in Indonesian Representative Offices abroad under the Ministry of Foreign Affairs. The evaluation employs the Human-Organization-Technology Fit (HOT-Fit) Model, which assesses the human, organizational, and technological aspects of information system implementation. This research utilized a qualitative research method. Data was collected through interviews, observations, and document reviews. Qualitative data analysis was conducted following the method described by Miles and Huberman. This study highlights the contributions of human and organizational factors in enhancing the implementation of SAKTI for the preparation of agency-level financial statements. The findings reveal that the SAKTI application is effective in supporting government accounting and simplifying the financial reporting process at Indonesian Representative Offices abroad under the Ministry of Foreign Affairs.